Improving the Ability to Recognize Different Colors Using Small Balls - Eni Lovita; Dwi Rulismi; Lydia Margaretha; Mimpira Haryono; Ranny Fitria Imran (Journal Of Dehasen Educational Review, 2026)
This study aimed to improve children's ability to recognize various colors through the use of small ball media at PAUD Pelita Bunda, Arang Sapat Village, Lubuk Sandi District, Seluma Regency. The study employed a Classroom Action Research (CAR) method using the John Elliot model, which was conducted in two cycles consisting of planning, action, observation, and reflection. The research participants were 15 children, comprising 8 boys and 7 girls. Data were collected through observation, documentation, and field notes, while data were analyzed using descriptive quantitative and descriptive qualitative techniques. The findings indicated that the children's ability to recognize various colors improved in each cycle. In Cycle I, the children obtained a score of 134 out of a maximum score of 180, with a percentage of 74.44%, which was categorized as Developing as Expected. After improvements were made in Cycle II, the score increased to 177 out of 180, with a percentage of 98.00%, which was categorized as Very Well Developed. Therefore, the use of small ball media was proven to be effective in improving children's ability to recognize various colors, including identifying, naming, and classifying colors, at PAUD Pelita Bunda, Arang Sapat Village, Lubuk Sandi District, Seluma Regency.